Experimental infection of cattle with Mycobacterium tuberculosis isolates shows the attenuation of the human tubercle bacillus for cattle - Villarreal-Ramos, B; Berg, S; Whelan, A; Holbert, S; Carreras, F; Salguero, F; Khatri, B; Malone, K; Rue-Albrecht, K; Shaughnessy, R; Smyth, A; Ameni, G; et al. (Nature Publishing Group, 2018)
The Mycobacterium tuberculosis complex (MTBC) is the collective term given to the group of bacteria that cause tuberculosis (TB) in mammals. It has been reported that M. tuberculosis H37Rv, a standard reference MTBC strain, is attenuated in cattle compared to Mycobacterium bovis. However, as M. tuberculosis H37Rv was isolated in the early 1930s, and genetic variants are known to exist, we sought to revisit this question of attenuation of M. tuberculosis for cattle by performing a bovine experimental infection with a recent M. tuberculosis isolate. Here we report infection of cattle using M. bovis AF2122/97, M. tuberculosis H37Rv, and M. tuberculosis BTB1558, the latter isolated in 2008 during a TB surveillance project in Ethiopian cattle. We show that both M. tuberculosis strains caused reduced gross pathology and histopathology in cattle compared to M. bovis. Using M. tuberculosis H37Rv and M. bovis AF2122/97 as the extremes in terms of infection outcome, we used RNA-Seq analysis to explore differences in the peripheral response to infection as a route to identify biomarkers of progressive disease in contrast to a more quiescent, latent infection. Our work shows the attenuation of M. tuberculosis strains for cattle, and emphasizes the potential of the bovine model as a ‘One Health’ approach to inform human TB biomarker development and post-exposure vaccine development.